The Use of Plumbing Tools Saving Water With Efforts to Save Clean Water With Application of Green Building Concept at Menara Cibinong Apartment - Wahyudi, Wahyudi (Journal of Architectural Research and Education, 2019)
The developing of construction in Bogor Regency affected by citizen’s growth caused by urbanization. Citizen’s growth of Bogor Regency is estimated to reach 5.9 million people in 2021. Menara Apartment Cibinong construction indirectly could be increasing water needs which affected domestic waste water amount. To minimalizing that problem, there is need to be a planning of plumbing system for clean water and waste water and also the green building concept. With the water conservation includes the reduction of water usage. This water saving plumbing device. The chosen Water Saving Plumbing Equipment because could be saving water up to 33% from initial water needs as amount 305.88 m3/day.Keywords plumbing, Green Building, water saving plumbing device